The Effect of Knowledge Levels of Breastfeeding Mothers About the Disease on Their Levels of Anxiety During the COVID-19 Pandemic Process - Tekiner, Selda Ayşe; Çullas Ilarslan, Nisa Eda; Günay, Fatih; Ceyhun Peker, Gülsen Ayşe (Frontiers in Public Health, 2022)
Introduction: During the COVID-19 pandemic, all age groups have been affected by the disease. Breastfeeding mothers are one of the groups that is affected most during this process. The current study aims to investigate the relationship between the knowledge levels of breastfeeding mothers about COVID-19 and their anxiety levels. Materials and Methods: Mothers who applied to the Pediatric Outpatient Department of Ankara University Medical Faculty Hospital in relation to their breastfed infants between July 1 and August 31, 2020 were included in the study. Questionnaires measuring the level of knowledge about COVID-19 disease and breast milk and questionnaires measuring anxiety levels were administered to mothers. The state-trait anxiety levels and knowledge levels of breastfeeding mothers about COVID-19 disease, as well as their knowledge levels about breast milk and sociodemographic characteristics were compared. Results: A total of 145 breastfeeding mothers were included in the study. The trait anxiety was found to be either absent or mild in 89 (61.4%), moderate in 28 (19.3%), and advanced in 28 (19.3%) mothers. The state anxiety level, however, was found to be either absent or mild in 51 (35.2%), moderate in 42 (29%), and advanced in 52 (35.9%) mothers. When mothers’ trait and state anxiety levels and their knowledge levels about breast milk, their knowledge levels about COVID-19 disease and their sociodemographic characteristics were compared, it was determined that mothers with 0-6 months old infants had lower state anxiety levels compared to mothers with older infants. However, the anxiety levels of mothers whose children were >12 months old were mostly moderate (p<0.05). There was no statistically significant difference in terms of other variables (p>0.05). A positive correlation was found between the child age and state anxiety level (p=0.027). Conclusion: Although the majority of mothers who are breastfeeding have been experiencing anxiety during the COVID-19 pandemic process, it seems that the level of anxiety in mothers who breastfeed their children over 12 months has become even more severe.